1988
DOI: 10.1161/01.cir.78.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Human right ventricular end-systolic pressure-volume relation defined by maximal elastance.

Abstract: This study was undertaken to determine 1) whether a combined radionuclide-hemodynamic technique could define the right ventricular end-systolic pressure-volume relation (RV ESPVR) in the clinical setting, 2) whether the human RV ESPVR defined by maximal elastance is linear and responsive to inotropic interventions, and 3) whether more easily measured modifications of the ESPVR are reliable substitutes as an index of RV function. Eight patients with normal RV function were studied with simultaneous micromanomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…18 Interestingly, despite having markedly different ventricular geometry and hemodynamics, many studies showed that the RV also follows a time-varying elastance model ( Figure 3). 19,20 Because of the different shape of RV pressure-volume curves, maximal RV elastance better reflects RV contractility than does the end-systolic elastance commonly used in LV pressure-volume interpretation. 20 On the basis of the study by Dell'Italia and Walsh, 20 the normal maximal RV elastance is 1.30Ϯ0.84 mm Hg/mL.…”
Section: Cardiodynamicsmentioning
confidence: 99%
“…18 Interestingly, despite having markedly different ventricular geometry and hemodynamics, many studies showed that the RV also follows a time-varying elastance model ( Figure 3). 19,20 Because of the different shape of RV pressure-volume curves, maximal RV elastance better reflects RV contractility than does the end-systolic elastance commonly used in LV pressure-volume interpretation. 20 On the basis of the study by Dell'Italia and Walsh, 20 the normal maximal RV elastance is 1.30Ϯ0.84 mm Hg/mL.…”
Section: Cardiodynamicsmentioning
confidence: 99%
“…A variety of physiological parameters can be derived from the pressure-volume loops. 23 Because the shape of the pressure-volume curve in the RV is different from that of the LV, maximal elastance (e max ) 24 better reflects RV contractile function than does the end-systolic elastance (Ees) commonly used to determine LV contractile function. 25 RV contractile function can also be measured as PRSW.…”
Section: Indexes Of Contractile Functionmentioning
confidence: 99%
“…The methodological prerequisites for determining all of the essential parameters of mechanical cardiac action in situ have been available for a long time -and have been improved considerably during the last few years, although some detailed problems remain to be solved (5,7,12,57,59,63,64). However, beyond a merely descriptive presentation ( Fig.…”
mentioning
confidence: 99%